On the Alpha Power Kumaraswamy Distribution: Properties, Simulation and Application - Ahmed, Mohamed Ali (Revista Colombiana de Estadística, 2020)
Adding new parameters to classical distributions becomes one of the most important methods for increasing distributions ﬂexibility, especially, in simulation studies and real data sets. In this paper, alpha power transformation (APT) is used and applied to the Kumaraswamy (K) distribution and a proposed distribution, so called the alpha power Kumaraswamy (AK) distribution, is presented. Some important mathematical properties are derived, parameters estimation of the AK distribution using maximum likelihood method is considered. A simulation study and a real data set are used to illustrate the ﬂexibility of the AK distribution compared with other distributions.